Entrance Surface Air Kerma (ESAK) in Adult Posteroanterior (PA) Chest Radiography: An Exploratory Analysis - Intan Mulia Sari; Irhamni Irhamni; Rini Safitri; Evi Yufita; Ariana Shafira Dewi (Talenta Publisher, 2026)
This study estimated Entrance Surface Air Kerma (ESAK) for adult posteroanterior (PA) chest radiography and described ESAK patterns in relation to selected technical parameters and patient characteristics as an initial facility-level baseline. A descriptive–exploratory observational study was conducted in 10 adult patients using a Siemens digital radiography system equipped with Automatic Exposure Control (AEC). ESAK was estimated from X-ray tube output obtained from acceptance/constancy testing and combined with routinely recorded exposure parameters. Incident air kerma (INAK) was calculated first and then converted to ESAK using a backscatter factor assumed to be constant at 1.35. All examinations were performed at 125 kVp with a fixed source-to-image distance (SID) of 180 cm. Focus-to-skin distance (FSD) was not recorded directly and was estimated from SID and the recorded chest thickness. ESAK ranged from 0.09 to 0.17 mGy (mean, 0.13 mGy), and all values were below the BAPETEN optimization reference level of 0.2 mGy. In this limited sample, graphical patterns indicated that ESAK increased with mAs and body weight and decreased with increasing FSD. These findings are preliminary and require confirmation in a larger cohort; however, they may serve as a temporary local baseline for internal dose auditing and to inform the design of subsequent dose optimization studies.